Advancing higher education students’ self-efficacy and achievement through self-directed learning integrated with the BOPPPS model - Yang, Yuming; Sriwisathiyakun, Kanyarat; Ratanaolarn, Thanin (My University, 2025)
As higher education increasingly prioritizes students’ self-directed learning (SDL) capabilities, enhancing self-efficacy has become a vital aspect of their development. This study investigated the effects of an integrated SDL-BOPPPS (Bridge-in, Objective, Pre-Assessment, Participatory Learning, Post-Assessment, and Summary) model on students’ self-efficacy and academic achievement utilizing a quasi-experimental design. The SDL-BOPPPS model received an average rating of 4.55 from five experts on a 5-point Likert scale, indicating that its quality met the teaching standards. In the quasi-experimental research, ninety students from The Open University of China were randomly assigned to experimental and control groups. The SDL-BOPPPS model was implemented in the experimental group over six weeks, structured around five stages: target setting, plan design, information collection, learning activity implementation, and reflection. Descriptive statistics and independent samples t-tests were employed for data analysis. The results revealed that students in the experimental group exhibited significantly higher levels of self-efficacy and achievement compared to those in the control group. These findings highlight the effectiveness of the SDL-BOPPPS model in enhancing self-efficacy and academic performance while providing new insights for integrating innovative teaching models into higher education contexts.
Keywords: achievement; BOPPPS model; higher education; Self-directed learning; self-efficacy